Hak Pendidikan Anak dan Kesadaran Hukum Masyarakat Mengenai Larangan Pernikahan di Bawah Umur - Sulaeman, Rian Rosita (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2019)
This research is directed to two main things namely, (1) factors that influence the occurrence of underage marriage in the village of Muncang. (2) the legal awareness of the community about underage marriage to chiidren’s education right. Methods of data collection: Interview, Observation and Documentation with a qualitative approach. Data analysis using data reductio), data display and conclusion drawing. The results showed that the factors affecting underage marriages were economic problems, there had been a soulmate, and fears of the parents would be undesirable. Regarding public awareness of the law can be said that society is not aware of the law especially for those who do underage marriages. This is because public awareness is limited to the knowledge of the understanding of underage marriages. The conclusion of the study is the legal awareness of Kampung Muncang community regarding the prohibition of underage marriage to the right of children's education can be said to be not aware of the law because only knowing about the notion of marriage under Without knowing the rules governing it. Then the relation to obtaining the right of education is, if they do the marriage before the specified age limit means they have not been able to get the maximum education they can.